1995
DOI: 10.1108/08876049510079871
|View full text |Cite
|
Sign up to set email alerts
|

Managing consumer expectations of low‐margin, high‐volume services

Abstract: Service firms operating on low margins per transaction must generate a high volume of business to survive the competitive environment of the 1990s. Firms must raise the expectations of consumers to increase patronage, then successfully meet these expectations. Examines the antecedents to consumer expectations of low‐margin, highvolume service firms, and gives managerial implications, illustrating how to manage a service firm, successfully operating on low margins successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…According to some researchers, a customer judges the quality of provided services IJCHM 21,3 based on the discrepancy among expectations and perceptions (Bitner, 1990;Clow and Beisel, 1995;Grönroos, 1984;Parasuraman et al, 1988). This concept led Parasuraman et al (1985Parasuraman et al ( , 1988 to identify five main service quality dimensions (reliability, responsiveness, empathy, tangibles and assurance) and to create the SERVQUAL scale, which consists of 22 questions measuring expectations and 22 questions measuring perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to some researchers, a customer judges the quality of provided services IJCHM 21,3 based on the discrepancy among expectations and perceptions (Bitner, 1990;Clow and Beisel, 1995;Grönroos, 1984;Parasuraman et al, 1988). This concept led Parasuraman et al (1985Parasuraman et al ( , 1988 to identify five main service quality dimensions (reliability, responsiveness, empathy, tangibles and assurance) and to create the SERVQUAL scale, which consists of 22 questions measuring expectations and 22 questions measuring perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…13 On the other hand, if their last experience was negative, their future expectations will be low, which can result in actions such as customers leaving the fi rm and negative word-of-mouth communications. 45 However, Clow and Beisel 45 found that this evaluation would also affect the image that customers have of the fi rm. Customers ' expectations of services and their evaluation of the service received are therefore infl uenced by the image they have of the fi rm.…”
Section: Expectationsmentioning
confidence: 96%
“…As the definitions imply, expectations relate to the future behaviour and have two dimensions: the anticipatory nature of expectations and their normative quality. Expectations are anticipatory in nature vis-a-vis the future performance of the product and normative in quality when they have become established via previously encountered situations (Clow and Beise 1995;Tutuncu 2001).…”
Section: Literature Reviewmentioning
confidence: 99%